How specific is specific self-efficacy? A construct validity study using Rasch measurement models. (June 2017) - Nielsen, Tine; Makransky, Guido; Vang, Maria Louison; Dammeyer, Jesper
Highlights: The Motivated Strategies for Learning Questionnaire Self Efficacy Scale found to be two separate valid subscales. Subscales measuring specific academic learning self-efficacy and exam self-efficacy. Differences in subscale scores dependent on university and admission methods. Subscales hold promise for more detailed studies of student self-efficacy. Abstract: Self-efficacy is an important and much used construct in psychology and social science studies. The validity of the measurements used is not always sufficiently evaluated. The aim was to evaluate the psychometric properties of the Danish translation of the self-efficacy subscale of The Motivated Strategies for Learning Questionnaire (MSLQ-SE) within a higher education context. Rasch measurement models were employed focusing on measurement invariance and dimensionality. Results with one students sample showed the MSLQ-SE to be not one, but two separate unidimensional subscales, measuring specific academic learning self-efficacy (SAL-SE) and specific academic exam self-efficacy (SAE-SE), each scale being measurement invariant relative to age, Gender, admission method and specific course targeted. Furthermore, significant and relevant differences between the SAL-SE and SAE-SE scores dependent on university and admission method were found, and these results were replicated with two further samples. The SAL-SE and SAE-SE scales hold promise for more detailed studies of student self-efficacy.